Pneumonia a major pediatric disease admitted from emergency department of Patan Hospital - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2018)
Introduction: In Nepal, annual incidence of pneumonia in under- five years children is 90/1000. So, this study is done to see thepediatric admission from emergency with the diagnosis of pneumonia in comparison to other admitting diagnosis. Method: This is a hospital based retrospective and descriptive study seeing the pediatric admission through emergency from April 2017 to March 2018. This study was conducted at department of general practice and emergency medicine department of Patan Academy of Health Sciences. Result: During one year period 39349 patients had visited emergency department and among them 5951(15%) got admission in different wards of this hospital and among all admitted patients, 887 got admitted to pediatric department, which is 2.2% of the total patients visiting emergency and 14.9% of admitted patients. Respiratory problem was the most common cause of admission 257(28.9%) amongst all pediatric admission Conclusion: Pneumonia was the most common cause of hospital admission in this study.